PENGARUH CORPORATE GOVERNANCE DAN CORPORATE REPUTATION TERHADAP EMPLOYEE ENGAGEMENT (Studi pada sebuah perusahaan logistik multinasional di Indonesia) - Haryanto Haryanto (Center for Economic Studies Universitas Katolik Parahyangan, 2020)
The purpose of this study was to determine whether there is a relationship between Corporate Governance and Corporate Reputation on Employee Engagement. This research was conducted at a multinational logistics company in Indonesia in December 2020. The data collection method was carried out by means of a questionnaire via google form which was distributed to employees. Data analysis was performed using Statistical Product and Service Solutions with classical tests. Researcher found several things, including Corporate Governance partially has a significant and positive effect on Employee Engagement, Partially Corporate Reputation has a significant and positive effect on Employee Engagement, Corporate Governance and Corporate Reputation simultaneously have a significant and positive effect on Employee Engagement.